Natural Infection by Trypanosoma cruzi in a Dog from Bahia State - Northeast of Brazil - Silva, Kaíque Pires Moura da; da Silva Rodrigues, Valquíria Tatiele; Ribeiro Junior, Gilmar José da Silva; Carneiro, Ianei de Oliveira; Gomes Júnior, Deusdete Conceição; Alves da Silva Vieira, Layze Cilmara (Acta Scientiae Veterinariae, 2020)
Background: Chagas Disease (CD) is a parasitic anthropozoonosis caused by the Trypanosoma cruzi (T. cruzi), a protozoan transmitted by insects from the Reduviidae family. Several species of wild and domestic animals, humans included, are susceptible, developing acute clinical signals (myocarditis and cardiac arrhythmias) or chronic signals (drop on the performance and syncope) of the disease. In Brazil, the disease in dogs shows variable indexes of occurrence. The present paper describes the natural infection by T. cruzi in a canine living in the city of Barra, in the state of Bahia, Brazil, a region classified as high risk of vulnerability for the CD in the northeast of Brazil. Case: A 9-year-old male dog, non-specific breed, was referred to the clinic the Veterinary Clinic for Small Animals, at the Veterinary Medical Teaching Hospital), at the Federal University of the West of Bahia. Its owner reported the presence of bloody secretion in the penile region. During the physical exam it was possible to observe an increase in the volume of the penis base. All of the animal’s physiological parameters were within normal levels. Blood samples and cytological laminas from the lesioned area were collected and sent to the Laboratory of Veterinary Clinical Pathology in the same institution. The cytological exam showed monomorphic population of great round cells with a round nucleus, condensed chromatin and one to two prominent nucleolus, abundant and slightly basophilic cytoplasm, with multiple stippled vacuoles, thus confirming a Transmissible venereal tumor (TVT) case. With the blood exam one observed a thrombocytopenia, neutrophilia with a deviation on the left and the presence of a trypomastigote form of Trypanosoma sp. in the blood smears. A complete blood sample was sent to the Laboratory of Pathology and Molecular Biology from the Fiocruz-BA (Oswaldo Cruz Foundation in the State of Bahia), being identified by the PCR technique, T. cruzi. Discussion: During the complete blood count, specifically using the blood smear, the microscopic visualization of the trypomastigote form of the Trypanosoma sp., a hemoparasite of filiform aspect, with undulating membrane over the whole body and free flagellum, confirming a case of trypanosomiasis. Such diagnostics had not been considered up to this moment, as the animal did not present any clinic symptomatology that indicated the pathological condition. The high levels of parasitemia presented by the animal, confirmed by the presence of the protozoan in the blood smear, probably indicate the acute phase of the infection, period in which the multiplication and development of the agent is higher, consequently allowing the visualization of the hemoparasite in the lamina. Although the TVT had proved to be the main derogatory factor of sanity and wellbeing of the animal, one calls the attention in this case for the trypanosomiasis, a zoonosis that causes great risk to the sole health, highlighting that the canine species is taken as an important reservoir of T. cruzi, relevant for the maintenance and interaction among the domestic and wild cycles of the Chagas Disease. This is the first report of a canine naturally infected by T. cruzi in the west Region of the State of Bahia. It is, thus, important to emphasize its significance once dogs can be reservoirs of the protozoan, acting in their life cycle and epidemiological chain of the Chagas Disease, enabling the infection of triatomines and humans. Future studies should be done with the purpose of determining the predominance of the agent in the region of the city of Barra, in the State of Bahia.